Impactos por PCBs em Orcinus orca: um problema mundial. - Amorim, Thiago Barros de (2022)
PCBs are one of the chemical compounds that most bring toxicity to organisms. The quantification of PCBs has been carried out in animals all over the world, mainly in the killer whale, Orcinus orca (Linnaeus, 1758). O. orca is a species of great longevity